Virtual Personality of a Moving Thatcherized Face - Barabanschikov V.A; Abramov A.D (Moscow State University of Psychology and Education, 2021)
The study explores the patterns of perception of a virtual model with a 'Thatcherized face'.Using the Deepfake IT-technology and the Adobe After Effects video editor, a stimulus model reproducing the face of a young actress with the eye and mouth areas inverted by 180° was created.It was shown that the phenomena of perception of the Thatcherized face, registered earlier under static conditions, are preserved when the dynamic model is exposed, and acquire a new content.In particular, the inversion effect in the dynamic mode is stronger than in the static one.Under multimodal exposure, its magnitude decreases, while the adequacy of the direct exposure evaluations increases.The age of the virtual model as compared to the real person is overestimated.The adequacy of evaluations of the models' gender and behavior exceeds 85%.Estimates of attractiveness and emotional states of the virtual models directly depend on the type of situation they are in.The similarity of the main patterns found in the study of the perceptions of Thatcherized and chimerical faces is demonstrated.